Successful Use of Low-Dose Combined Spinal-Epidural Anesthesia for Cesarean Section in a Parturient with Eisenmenger Syndrome: A Case Report - Sahala Trident Sitorus; Isngadi (HM Publisher, 2025)
Introduction: Eisenmenger syndrome (ES) in pregnancy is a catastrophic condition associated with maternal mortality rates of 30-50%. The profound physiological changes of pregnancy, particularly the decrease in systemic vascular resistance (SVR), exacerbate right-to-left (R-L) shunting, leading to severe hypoxemia and right ventricular failure. Anesthetic management is perilous, as both general and neuraxial anesthesia can precipitate hemodynamic collapse. Case presentation: We present the case of a 25-year-old G2P101Ab000 parturient at 32-34 weeks of gestation with ES secondary to a large secundum atrial septal defect and severe pulmonary hypertension. She presented for an urgent Cesarean section due to labor. A meticulous anesthetic plan was executed, centered on a low-dose Combined Spinal-Epidural (CSE) technique. This involved an intrathecal injection of 7.5 mg hyperbaric bupivacaine with 50 mcg fentanyl, followed by incremental epidural titration of 0.2% ropivacaine. Hemodynamic stability was proactively managed with inline infusions of phenylephrine and milrinone. The procedure was successful, maintaining stable maternal hemodynamics, SVR, and oxygen saturation. A healthy infant was delivered with APGAR scores of 7 and 8. The patient had an uncomplicated postoperative recovery. Conclusion: This case demonstrates that a carefully titrated, low-dose CSE technique, combined with invasive monitoring and proactive pharmacological support, can be a safe and effective strategy for Cesarean section in ES patients. This approach successfully navigates the hemodynamic dilemma by providing excellent analgesia while preventing a clinically significant drop in SVR.